A155 QUALITY OF CARE IN THE INFLAMMATORY BOWEL DISEASES (IBD) CENTER FROM A TERTIARY REFERRAL HOSPITAL: PATIENT ASSESSMENT STRATEGY AT REFERRAL. (1st March 2018) - Restellini, S; Gonczi, L; Kurti, Z; Afif, W; Bessissow, T; Wild, G; Seidman, E G; Kohen, R; Bitton, A; Lakatos, P L
Abstract: Background: IBD impacts substantially on patient's physical health, social functioning and quality of life. Aims: We aimed to analyze quality of care indicators (QIs) including structural and process QIs at referral in the McGill University Health Center (MUHC) IBD Center that includes 6 IBD specialists, 2 IBD nurses, 2 research nurses, and 2 IBD fellows with rapid access to colorectal surgeons and imaging. Methods: We retrospectively analyzed out- and inpatient records of all consecutive patient at the MUHC IBD clinic between June and December 2016. Demographic variables, outpatient visits, inpatient stays, laboratory, imaging and endoscopy data, medications history, and vaccination profile were captured. Results: 653 patients (46.2% men, 66.6% Crohn's disease (CD), age at referral: 41.3 years) were included. At referral 38% of CD patients had L3 classification, 46% complicated behaviors (B2 or B3) and 22% perianal disease.31% and 40% of UC patients had extensive and moderate-to severe disease, respectively. 60% of patients had a documented previous ileocolonoscopy at referral, 10% MRI and 28% CT. 16% of patients were on biologics. 66% had an ER visit, 45% required hospitalization, while 30% of CD patients had IBD-related surgery in the past. 78% of patients were employed. Patients were objectively re-evaluated at referral: 81% underwent ileocolonoscopy, 13% upper GI endoscopy, 31% of CD patients had abdomino-pelvic MRI or CT and 15% abdominal US. CBC, CRP and FCAL were measured in 85%, 75% and 24%, respectively. Medical therapy was changed in 55% (active disease: 78%, remission: 22%) with a maximum therapeutic step of biologics in 32%. 10% of patients required hospitalization while 5% surgery at referral. Conclusions: Our data support that a tight monitoring was applied at the MUHC IBD center including a high emphasis on objective patient (re)evaluation, and accelerated treatment strategy already at referral. Funding Agencies: NoneMcGill University Healtch Center (MUHC) Department of Medicine CAS Research Grant